2006
DOI: 10.1002/jnr.20972
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of JL 13, a potential atypical antipsychotic, on rat dopamine and serotonin receptor subtypes

Abstract: Changes in dopamine (DA) D(1), D(2), D(3), and D(4) receptors and serotonin 5-HT(1A) and 5-HT(2A) receptors in rat forebrain regions were autoradiographically quantified after continuous infusion of JL 13 [(5-(4-methylpiperazin-1-yl)-8-chloro-pyrido[2,3-b][1,5]benzoxazepine fumarate] for 28 days with osmotic minipumps and compared with the effects of other typical (fluphenazine) and atypical (clozapine, olanzapine, and risperidone) antipsychotic drugs from previous studies. Similar to other typical and atypica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Reductions in NMDA receptor binding induced by JL 13 and other atypical antipsychotics in the CPu may arise from neurochemical changes initiated by well-documented interactions of these drugs with dopamine or serotonin systems, both of which may modulate glutamatergic neurotransmission (Aghajanian and Marek 2000;Carlsson et al 2001). In support of this hypothesis, we recently found that repeated treatment with JL 13 increased abundance of 5-HT 1A receptors and decreased 5-HT 2A receptor levels in rat frontal cortex (Moran-Gates et al 2006). JL 13-induced changes in concentrations of these 5-HT receptors in cerebral cortex may suppress Glu neurotransmission in corticostriatal …”
Section: Effects Of Jl 13 Treatment On Nmda Receptorsmentioning
confidence: 83%
See 4 more Smart Citations
“…Reductions in NMDA receptor binding induced by JL 13 and other atypical antipsychotics in the CPu may arise from neurochemical changes initiated by well-documented interactions of these drugs with dopamine or serotonin systems, both of which may modulate glutamatergic neurotransmission (Aghajanian and Marek 2000;Carlsson et al 2001). In support of this hypothesis, we recently found that repeated treatment with JL 13 increased abundance of 5-HT 1A receptors and decreased 5-HT 2A receptor levels in rat frontal cortex (Moran-Gates et al 2006). JL 13-induced changes in concentrations of these 5-HT receptors in cerebral cortex may suppress Glu neurotransmission in corticostriatal …”
Section: Effects Of Jl 13 Treatment On Nmda Receptorsmentioning
confidence: 83%
“…These findings support the hypothesis that AMPA receptors in these brain regions constitute common targets that mediate the actions of JL 13 and newer antipsychotic agents. Atypical-like profile of JL 13 on ionotropic Glu receptors, as well as dopamine and serotonin receptor subtypes (Moran-Gates et al 2006), further support the development of JL 13 as a novel atypical antipsychotic drug for the improved treatment of schizophrenia and other idiopathic psychotic disorders.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations